PENERAPAN MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE (VCT) BERBANTUAN MEDIA VIDEO DAN PENGARUHNYA TERHADAP HASIL BELAJAR SISWA - Mutmainnah, Mutmainnah; Herianto , Edy; Fauzan , Ahmad; Ismail , M (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine whether there is an influence of the application of the Value Clarification Technique (VCT) learning model assisted by video media on the learning outcomes of class VIII students in Civics subjects at SMP Negeri 4 Kopang. The approach used is a quantitative approach with a quasi-experimental type and a one group pre-test and post-test design. The population was class VIII, and the research sample was class VIII A. The research instruments used were multiple choice and fill-in-the-blank questions. The data collection techniques used are observation, documentation and tests. Data analysis uses prerequisite tests in the form of normality tests, homogeneity tests, and hypothesis tests using the t-test. After carrying out the prerequisite tests, the results showed that the data was normally distributed and homogeneous and the results of the hypothesis test obtained a value of tcount > ttable (4.189 > 2.110), meaning that Ha was accepted and Ho was rejected. Thus, there is an influence of the application of the Value Clarification Technique (VCT) learning model assisted by video media on the learning outcomes of class VIII students in Civics subjects at SMP Negeri 4 Kopang.